Factors Influencing the Utilization of the Mobile JKN Health Application in Indonesia - Rahmadani, Suci; Feisha, Alifa Lulu; Palutturi, Sukri; Balqis, Balqis; Abadi, Muh. Yusri (Journal of Public Health and Pharmacy, 2025)
Introduction: The Indonesian Health Social Security Administering Agency (BPJS) has developed an information technology-based service, Mobile JKN, which can be accessed via smartphone. This application can make obtaining program services easier for National Health Insurance participants. However, utilization of the Mobile JKN application is still lacking; only 6.8% of National Health Insurance Participants in Ternate City use this application. This research aims to determine the factors related to using the Mobile JKN application at BPJS Health in Ternate City. Methods: This type of research is quantitative, using an analytical survey method and a cross-sectional study. A sample of 265 was obtained by chance through direct interviews and online questionnaires on Google Forms. Univariate data analysis with frequency distribution and bivariate analysis using Fisher's exact test. Results: The research found a relationship between system quality (p=0.001), information quality (p=0.000), service quality (p=0.000), user satisfaction (p=0.000), and net benefits (p=0.000) with the use of the Mobile JKN application. These findings highlight the critical role of technical and user experience factors in driving app adoption. Conclusion: All research variables were related to using the Mobile JKN application. The information system for the Mobile JKN application must be developed to be more easily accessible to all groups of society. To improve utilization, efforts should focus on enhancing accessibility, user-friendliness, and digital literacy, especially for underserved populations. Strengthening infrastructure and nationwide awareness campaigns can further drive adoption. These findings provide valuable insights for policymakers and serve as a model for similar digital health initiatives globally.